1989
DOI: 10.1152/ajpendo.1989.256.1.e159
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and postabsorptive hepatic glucose and insulin metabolism in hyperthyroidism

Abstract: The effect of thyroid hormone excess on hepatic glucose balances and fractional hepatic extraction of insulin and glucagon was examined in six conscious dogs with catheters in the portal vein, hepatic vein, and femoral artery and Doppler flow probes on the portal vein and hepatic artery. An oral glucose tolerance test was performed before and after the animals were made hyperthyroid by intramuscular thyroxine administration (100 micrograms.kg-1.day-1) for 10 days. In the basal state and after oral glucose, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…Animal studies have revealed that hyperthyroid animals develop elevated plasma glucose and insulin levels, due to increased hepatic glucose production including increased gluconeogenesis and glycogenolysis (Raboudi et al, 1989), and decreased glucose clearance and disposal. In human patients with Grave's hyperthyroidism, glucose tolerance is impaired (Randin et al, 1985).…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…Animal studies have revealed that hyperthyroid animals develop elevated plasma glucose and insulin levels, due to increased hepatic glucose production including increased gluconeogenesis and glycogenolysis (Raboudi et al, 1989), and decreased glucose clearance and disposal. In human patients with Grave's hyperthyroidism, glucose tolerance is impaired (Randin et al, 1985).…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…While Thyroid hormones oppose the action of insulin and stimulate hepatic gluconeogenesis and glycogenolysis 12,13 they upregulate the expression of genes such as GLUT-4 and phosphoglycerate kinase involved in glucose transport and glycolysis respectively, thus acting synergistically with insulin facilititating glucose disposal and peripheral utilisation. 14,15 In hypothyroidism, glucose homeostasis is also affected although its clinical impact is less obvious.…”
mentioning
confidence: 99%
“…Functional condition of thyroid was evaluated by determining the basal serum concentrations of TSH, FT 4 and FT 3 of patients, using enzyme-linked immunosorbent assay (ELIZA) with the help of test-system of company Roche Diagnostics (Switzerland) on automatic analyzer Cobas 6000 (e 601 module).…”
Section: Methodsmentioning
confidence: 99%
“…By "insulin resistance" (IR) we traditionally mean the altered tissue response to endogenous insulin, that is manifested by impaired glucose uptake in the adipose tissue and skeletal muscles, as well as suppression of hepatic gluconeogenesis [4]. Recent studies show that we can recognize IR not only in the pathogenesis of type 2 diabetes mellitus but also in many other pathological conditions, such as polycystic ovary syndrome, arterial hypertension, atherosclerosis, non-alcoholic steatohepatitis, etc.…”
Section: Introductionmentioning
confidence: 99%